IMPLEMENTASI TOOL WEKA DALAM CLUSTERISASI TINGKAT KEPATUHAN PENGGUNAAN ATRIBUT SEKOLAH - Muhammad Tafsir; Noliza Safitri Noliza Safitri (ITP Press, 2023)
Education means something that is crucial in life which aims to be able to improve the quality of human resources (HR). School is a learning home for students. Schools have a very important role and a sizable responsibility where schools must make students safe and comfortable and train all students in terms of discipline, one of which is the use of school attributes. All components related to the school must comply with all existing regulations. This study focuses on the use of attributes that should and must be used by all students every Wednesday in brown batik pants, using school symbols or logos, student names, flags, ranks and black shoes and socks. Based on this, this research was conducted to create a system with the clustering method to classify obedient and non-compliant classes and students in the use of attributes. The algorithm used is K-Means and data processing uses the Weka tool. The data generated and processed in this study were 61 data based on data on Wednesday 15 February 2023. The results of this study using the Weka processing tool showed that cluster 0, namely as many as 3 classes with indiscipline in the use of attributes, was absent and incomplete. While cluster 1 is as many as 23 classes with no and incomplete use of attributes. As for cluster 2, there are 35 classes with indiscipline in the use of no and incomplete attributes.